Major Sedimentary facies of the Miocene Formations and their Relation with Oil Production in the Central Euphrates depression - Albub, Samer Mostafa; Obaidi, Rami Ahmad (Journal of natural sciences, life and applied sciences, 2019)
This research Deals with the identification of the major rocky facies of the Miocene Sedimentary formations in the central Euphrates depression, The purpose is determining the nature of these facies, their components, their spread, reservoir properties and their role in the generation and storage of oil and natural hydrocarbons. To achieve this, the methodology of the petrological study was applied to 60 Cores from the deep drilling samples of the Al-Mahash oilfields, which underwent chemical reactions with acids and reagents to determine the initial mineral structure of the rock, physical experiments and petrophysical measurements to determine the severity and porosity, and microscopic petrological study (by polarized microscope) done by using 248 microscopic rocky sections. The results were presented and recorded in composite records. The study showed the presence of eight major sedimentary facies in the Miocene formations, in the central Euphrates depression, which are: the calcareous facies, dolomitic calcareous, dolomitic, calcareous affluent of gypsum and anhydrite, evaporative, marl and Argillaceous calcareous and Argillaceous facies. The study also showed the role of the rocky facies in generating, covering and storing the natural hydrocarbons. reservoir carbonate facies accounted about 29% of the general lithological column of the Miocene formations, and concentrated in Jeribe and Transition zone Formations. Total porosity values ​​reached 30% in some highly cleft dolomite levels. The hydrocarbon generation capability was limited to a few sparse thicknesses, for some organic Argillaceous and calcareous deposits, concentrated at the bottom of jeribe and Euphrates formations. The nature of the rocky coverings of the reservoir was defined, composed of evaporators, by a thickness of about 37% of the general lithological column, which have a little presence in the upper levels of Debbane, Jeribe and Transition zone formations, and great abundance in the Lower Fars formation. Very limited horizontal changings in the facies and thickness of the Miocene sedimentary formations were observed along the field, , by correlation between the lithological columns. The correlation showed the effect of these changings on the generation, storage and production of oil and hydrocarbons in the Miocene sediments.